Arabic Apology Expressions in English - Amer, Layali Amer Yahya; Mangatur Nababan; Muhammad Yunus Anis (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2025)
The translation of speech acts, particularly apologies, presents a significant challenge due to their cultural specificity. This study attempts to examine the translation techniques utilized to render apology utterances at the micro level in Naguib Mahfouz’s novel “Sugar Street.” Using a descriptive qualitative method, apology expressions identified in the Arabic source text and their English translations were analyzed according to Molina and Albir’s (2002) classification of translation techniques. The investigation found 51 instances of translation techniques applied to 10 apologetic utterances, some of which required more than one technique. The study showed that the most frequently used strategy was